Panhematin provides a therapeutic benefit in experimental pancreatitis. Issue 5 (15th December 2010) - Habtezion, Aida; Kwan, Raymond; Akhtar, Ehsaan; Wanaski, Stephen P; Collins, Stephen D; Wong, Ronald J; Stevenson, David K; Butcher, Eugene C; Omary, M Bishr
Abstract : Background and aim: Acute pancreatitis (AP) can result in pancreatic necrosis and inflammation, with subsequent multi-organ failure. AP is associated with increased neutrophil recruitment and a rise in pro-inflammatory cytokines such as TNFα. Pretreatment with haemin, results in recruitment of haem-oxygenase-1 (HO-1) + macrophages and protects against experimental pancreatitis. It is not clear whether modulation of HO-1 after onset of disease has a protective role. In this study, we tested the utility of Panhematin, a water-soluble haemin formulation, in activating and inducing pancreatic HO-1, and as a therapeutic agent in treating mouse acute pancreatitis. Methods: We defined the distribution of radiolabelled haemin, then used in vivo HO-1–luciferase bioluminescence imaging and the CO-release assay to test Panhematin-induced upregulation of HO-1 transcription and activity, respectively. Using two well-defined AP murine models, we tested the therapeutic benefit of Panhematin, and quantified cytokine release using a luminex assay. Results: Intravenously administered Panhematin induces rapid recruitment of HO-1 + cells to the pancreas within 2 h and de novo splenic HO-1 transcription by 12 h. Despite high baseline spleen HO-1 activity, the pancreas is particularly responsive to Panhematin-mediated HO-1 induction. Panhematin-treated mice, at various time points after AP induction had significant reduction in mortality, pancreatic injury, together with upregulation of HO-1 and downregulation of pro-inflammatory cytokines and CXCL1, a potent neutrophil chemoattractant. Conclusions: Despite AP-associated mortality and morbidity, no effective treatment other than supportive care exists. We demonstrate that Panhematin leads to: (i) rapid induction and activation of pancreatic HO-1 with recruitment of HO-1 + cells to the pancreas, (ii) amelioration of AP even when given late during the course of disease, and (iii) a decrease in leucocyte infiltration and pro-inflammatory cytokines including CXCL1. The utility of Panhematin at modest doses as a therapeutic in experimental pancreatitis, coupled with its current use and safety in humans, raises the potential of its applicability to human pancreatitis.